Salivary and Serum Leptin Concentrations in Patients With Chronic Periodontitis. Issue 4 (1st April 2015) - Purwar, Parth; Khan, M.A.; Mahdi, Abbas Ali; Pandey, Shivani; Singh, Babita; Dixit, Jaya; Sareen, Sagar
Abstract : Background: The discovery of leptin has led to the elucidation of a robust physiologic system that not only maintains fat stores but is also an integral part of the host defense mechanism. However, leptin concentrations in the saliva of patients with chronic periodontitis (CP) has not been explored despite the potential role of salivary biomarkers in determining the presence, risk, and progression of periodontal disease. Methods: Eighty‐four participants (44 with generalized severe CP and 40 without periodontitis) were enrolled. For each patient, the values of periodontal parameters were recorded, such as plaque index (PI), gingival index (GI), probing depth (PD), clinical attachment loss (AL), and percentage of sites with bleeding on probing (BOP) and clinical AL ≥5 mm. Saliva and serum samples were collected to estimate the leptin concentrations using enzyme‐linked immunosorbent assay kits. Statistical analysis was performed using software. Results: Participants with CP demonstrated significantly higher BOP, PI, GI, and percentage of sites with clinical AL >5 mm ( P <0.05). Leptin was detectable in all the clinical samples. Salivary leptin concentrations in patients with CP were significantly lower than in healthy volunteers (6, 200.61 ± 2, 322.11 versus 8, 799.60 ± 901.70 pg/mL), whereas serum leptin concentrations were significantly higher in patients with CP than in healthy volunteers (11, 600.00 ± 1, 705.01 versus 7, 616.62 ± 1, 169.83 pg/mL). In addition, the results reflected a significant negative correlation of salivary leptin and a positive correlation of serum leptin with PD ( P <0.05). Conclusion: The results suggest that leptin concentrations in saliva and serum are significantly altered in CP and relate closely to current disease activity; however, further studies are needed to confirm the findings.